2020
DOI: 10.1002/cam4.3267
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and practice patterns for male breast cancer compared with female breast cancer in Japan

Abstract: Male breast cancer (MBC) is rare, representing fewer than 1% of all breast cancer in the United States 1 ; however, recent trends show increased incidence. 2 Epidemiological differences in male and female breast cancer (FBC), such as an older age and a higher stage at diagnosis in MBC patients have been noted. Additionally, there is a higher chance of MBC being hormone receptor-positive and a lower chance of exhibiting human epidermal growth factor receptor-2 (HER2) overexpression. 2-5 Consequently, cancer tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…In comparison with women, men with BC tend to be diagnosed at an older age, for both early and advanced disease, with a median age at diagnosis ranging between 60 and 70 years, compared to 55–60 years in women [ 12 , 26 , 27 , 28 ]. Black men are more likely to be younger when diagnosed and have worse survival rates than their White counterparts [ 29 , 30 , 31 ].…”
Section: Epidemiology and Non-genetic Risk Factors For Mbcmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with women, men with BC tend to be diagnosed at an older age, for both early and advanced disease, with a median age at diagnosis ranging between 60 and 70 years, compared to 55–60 years in women [ 12 , 26 , 27 , 28 ]. Black men are more likely to be younger when diagnosed and have worse survival rates than their White counterparts [ 29 , 30 , 31 ].…”
Section: Epidemiology and Non-genetic Risk Factors For Mbcmentioning
confidence: 99%
“…At diagnosis, men with BC tend to present a more advanced stage of the disease when compared with women, usually with tumors >2.0 cm and positive axillary lymph nodes [ 26 , 27 ]. Many factors can explain the late diagnosis in men: absence of screening programs, lack of awareness about the condition by male population, embarrassment due to a stigmatization of the disease, and misjudgment by primary care physicians [ 20 , 46 , 47 , 48 ].…”
Section: Mbc Disease Characteristicsmentioning
confidence: 99%
“…Unlike the mature and profound management of female breast cancer (FBC) (Emens, 2018; McDonald et al, 2016), the main diagnosis and treatment of MBC are extrapolated from our knowledge of female counterpart. According to many researches, MBC patients were at later stage when they were diagnosed, they were older than female patients and less likely to receive standard therapy (Giordano, 2005; Ishii et al, 2020), the improvement of survival for them was poorer than female patients (Anderson et al, 2010; Ellington et al, 2020). Metastasis is the main culprit that leads to poor prognosis (DeSantis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Turkey reported that the median age at presentation was 62 years (range, 35-90 years) [57]. The mean age of the male breast cancer incidence was 63.3 years in Japanese males; however, at diagnosis, the mean age of Japanese MBC patients was 70 years [58,59], whereas in US MBC patients, the mean age at diagnosis 10 International Journal of Breast Cancer was 67 years [60]. In the Southern China region, the age at diagnosis in male patients was 64.5 years, whereas in the northern China region, it is 62 years (range, 24-84 years) [61,62].…”
Section: Discussionmentioning
confidence: 99%